Digital technology in medical visits: a critical review of its impact on doctor-patient communication - Marino, Filomena; Alby, Francesca; Zucchermaglio, Cristina; Fatigante, Marilena (Frontiers in Psychiatry, 2023)
With the rapid advances of digital technology, computer-mediated medical practices are becoming increasingly dominant in medical visits. However, the question of how to ensure effective, patient-centered communication in this transition remains crucial. In this mini-review, we explore this topic by reviewing quantitative and surveybased studies, as well as discursive-interactional studies that focus on the visit as a communicative event. The review is organized into four sections: the introductory section provides a brief synthesis of the two main models used in medical practice and describes the effects of patient-centered communication practices on patients' health and wellbeing. The second section presents and discusses qualitative and quantitative studies that assess the effect of technology on medical interaction and its impact on patient-centered communication. The third section focuses on whether and how the digital medical record represents a "potential communication risk" during doctor-patient interactions and explores how certain pen-and-paper literacy practices could help mitigate these challenges. In the concluding section, we outline and analyze three key considerations for utilizing technologies to foster and enhance patient-centered communication during medical visits.